Differences In Effectiveness Between Breast Massage And Combination Massage In Breast Milk Production In Postpartum - Adriana Egam; Yustitio Nora Veronica (Universitas Nahdlatul Ulama Surabaya, 2023)
The lack of exclusive breastfeeding in Indonesia, which is relatively low, could happen because various factors, in particular, influence the lack of care for breasts with method massage. However, until now, a study has not yet been conducted about the eligibility and acceptance of massage with Massage combination relation in increasing the volume of breast milk in postpartum mothers in the district Sorong. Research design is a quasi-experiment with two groups post-test design approach. Subject research is postpartum mothers who have babies 0 months old method taking sample study using accidental sampling. Data analysis in a study this T-test was performed. Obtained value (Sig. (2-tailed)) = 0.00, where in group massage combination capable increase the volume of breast milk by an average score of 75.30 compared with massage breast with an average volume of breast milk of 33.65. it means there is a difference Between massage breasts with massage combination in increasing the volume of breast milk.